Melão rendilhado fertirrigado por sistema de gotejamento e doses de silício em ambiente protegido - Lozano, Cláudia Salim (2017)
This work was conducted from November 12, 2015 to February 19, 2016, in a protected environment at the Technical Center of Irrigation (CTI), belonging to the Department of Agronomy (DAG) of the State University of Maringá - UEM. The objective was to quantify the water consumption, the crop coefficients and also to evaluate the effects of three slides of water and five doses of silicon, applied by drip fertigation during the development of the net melon plant, Sunrise hybrid. The first experiment did not fit any statistical design, because no treatments were tested, only direct reads of crop evapotranspiration (ETc) were carried out by means of a constant water table lysimeter. The reference evapotranspiration (ETo) was calculated by the Penman-Monteih-FAO method and the mean values of the crop coefficient (Kc). In the second experiment the experimental design was in randomized blocks (DBC) in a 5 x 3 factorial scheme, resulting in 15 treatments, with four replications. The first factor consisted of five doses of silicon (0, 50, 100, 150 and 200 kg ha-1) and the second factor of three water slides (40, 70 and 100% ETc). The mean fruit mass, transverse and longitudinal diameter of the fruit, transverse and longitudinal diameter of the locule, fruit shape index, locule index, pulp thickness and productivity were evaluated. Some chemical parameters, such as pH, soluble solids content, titratable acidity and soluble solubility ratio and titratable acidity ("ratio") were also evaluated. The total water consumption of the melon crop was 295 mm. The recommended Kc values of the melon cultivated in protected environment in the municipality of Maringá - PR, are 0,87; 1.15; 0.64 for the initial, intermediate and final stages, respectively. The water slides and the applied silicon doses did not influence the values of mean fruit mass, transverse and longitudinal diameter of the fruit, transverse and longitudinal diameter of the locule, fruit shape index, locule index, pulp thickness and productivity . The water depth of 100% of the evapotranspiration of the melon crop promoted higher values of soluble solids and ratio.